The Art of Adaptation in Film and Video Games - Thomas, Christian (MDPI Books, 2022)
This Special Issue of Arts explores the art and practice of adaptation in several different mediums with a focus on film and video games. The topics covered include experimental game design, narrative design, film and trauma, games adapted from literature, video game cinema, film and the pandemic, film and the environment, film and immigration, and film and culture.
Keywords: Mulan; adaptation; Disney; Orientalism; cultural authenticity; cultural palimpsest; Chinese cinema; science fiction; The Wandering Earth; patricide; patrilineality; nationalism; media; mass culture; film; digital games; film adaptation; experimental game design; game design process documentation; T.S. Eliot; Prufrock; remediation; comic strip; animated film; split screen; video poem; YouTube dramatic monologue; photographic montage; Contagion; propaganda; pandemic; premediation; Steven Soderbergh; Scott Z. Burns; transit; migrants; empathy; liminal spaces; Bildungsroman; modernity; videogames; Shakespeare; Tale of a Forest; biodiversity; documentary; ecocriticism; environmental narrative; forest; nature photography; nostalgia; species; video games; game studies; Star Wars; George Lucas; game reviews; criticism; thematic analysis; Japanese video games; game localization; cultural adaptation; localization approaches; localization strategies; domestication; foreignization; reception; trauma; origin; psychoanalysis; repetition; impossibility; loss; representation; extremity; writing; image; failure; memoir; missed experience; creative writing studies; screenwriting; video game narrative design; interactive writing; horror film; horror video games; survival horror; character development; sci-fi; thriller; genre; tropes; methodology; Film; TV & radio